Analysis of Factors Influencing Community Participation in Sustainable Forest Management in BKPH Mojorayung, Madiun - Ramadhani, Savira Pramesti; Sundawati, Leti; Kuncahyo, Budi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The success of sustainable forest management is inseparable from community participation as the leading actor in the Social Forestry Program. Various factors, including internal factors from the community and external factors, affect the participation of the community. Factors impacting community participation in sustainable forest management were analyzed in this study. The study was conducted at BKPH Mojorayung, KPH Madiun, East Java Regional Division Perum Perhutani, from April to June 2022, using a survey method with 242 randomly selected respondents. Partial Least Squares (PLS) analysis was conducted with the SmartPLS software. Based on the results, it was found that three factors impact the community's participation in forest management: the empowerment process accuracy, the role of community empowerment workers, and the support of group leaders. The characteristics of the communities around the forest did not affect community participation in forest management. Community participation also affects the sustainability of forests.